PENGARUH PEMBERIAN FEED ADDITIVE SEBAGAI PENGGANTI ANTIBIOTIK TERHADAP KONSUMSI PAKAN DAN PERTAMBAHAN BOBOT BADAN AYAM BROILER - Kurniawan, Jefry; Tugiyanti, Elly; Susanti, Emmy (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of this research was to determine the effect substitute for antibiotics on the consumption of feed and broiler chicken body weight gain. Materials and Methods. Experimental material using 120 DOC tails divided into 24 cage units. The maintenance phase is done 2 phases, namely the starter phase when the doc until the 14th day, then the treatment phase starts the day 15 to the age of 35 days. The study used a complete randomized design (RAL) with an antibiotic treatment (P0) Olaquindox of 0.125%, Probiotics (P1) Promix 0.2%, Phytobiotics (P2) (garlic flour 0.04%, 0.8% turmeric, and ginger 0.8%), and acidifier (P3) Acidtec 401 1% each treatment was repeated 6 times. Drinking water is given in Ad Libitum. Results. The results of the study indicate that the additive feeding in the ration does not have a significant effect (P> 0.05) on the consumption of feed and broiler chicken body weight gain. The results of the average feed consumption of feed namely P0 = 1997,02 ± 337,17 g/head, P1 = 1809,83 ± 118,61 g/head, P2 = 1884,13 ± 97,61 g/head, and P3 = 1879,50 ± 146,60 g/head. The results of the average weight of the body weight, namely P0 = 1322,82 ± 177,89 g/head, P1 = 1114,60 ± 74,80 g/ head, P2 = 1261,28 ± 151,28 ± 151,97 g/head, and P3 = 1240,23 ± 129,42 g/head. Conclusion. Additional feed additives such as probiotics, phytobiotics, and acidifiers in feed are able to replace the role of antibiotics to optimize the consumption of feed and body weight gain.